Morphology, structural, thermal, and tensile properties of bamboo microcrystalline cellulose/poly(lactic acid)/poly(butylene succinate) composites - Rasheed, Masrat; Jawaid, Mohammad; Parveez, Bisma; Bhat, Aamir Hussain; Alamery, Salman (MDPI, 2021)
The present study aims to develop a biodegradable polymer blend that is environmentally friendly and has comparable tensile and thermal properties with synthetic plastics. In this work, microcrystalline cellulose (MCC) extracted from bamboo-chips-reinforced poly (lactic acid) (PLA) and poly (butylene succinate) (PBS) blend composites were fabricated by melt-mixing at 180 °C and then hot pressing at 180 °C. PBS and MCC (0.5, 1, 1.5 wt%) were added to improve the brittle nature of PLA. Field emission scanning electron microscopy (FESEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscope (FTIR), thermogravimetric analysis (TGA), differential thermogravimetry (DTG), differential scanning calorimetry (DSC)), and universal testing machine were used to analyze morphology, crystallinity, physiochemical, thermal, and tensile properties, respectively. The thermal stability of the PLA-PBS blends enhanced on addition of MCC up to 1wt % due to their uniform dispersion in the polymer matrix. Tensile properties declined on addition of PBS and increased with MCC above (0.5 wt%) however except elongation at break increased on addition of PBS then decreased insignificantly on addition of MCC. Thus, PBS and MCC addition in PLA matrix decreases the brittleness, making it a potential contender that could be considered to replace plastics that are used for food packaging.